2006
DOI: 10.1002/ejic.200501020
|View full text |Cite
|
Sign up to set email alerts
|

Fe3GeTe2 and Ni3GeTe2 – Two New Layered Transition‐Metal Compounds: Crystal Structures, HRTEM Investigations, and Magnetic and Electrical Properties

Abstract: Fe3GeTe2 and Ni3GeTe2 are two new air‐stable, black‐metallic solids. They were characterized by single‐crystal X‐ray crystallography, high resolution transmission electron microscopy (HRTEM), and preliminary magnetic measurements. Both compounds crystallize in the hexagonal system [P63/mmc, Z = 2; Fe3GeTe2: a = 399.1(1) pm, c = 1633(3) pm;Ni3GeTe2: a = 391.1(1) pm, c = 1602.0(3) pm], and represent a new structure type with a pronounced macroscopic and microscopic layer character. They show close structural rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
305
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 337 publications
(341 citation statements)
references
References 13 publications
34
305
2
Order By: Relevance
“…Consistent with this, we refine a larger concentration of vacancies on Fe(2) compared to Ref. 18, and our refined U 11 for Ge is also larger than previously reported. However, the previous study did report a strong anisotropy for the displacement parameters of Ge, and a similar U 33 to that shown in Table II was reported.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with this, we refine a larger concentration of vacancies on Fe(2) compared to Ref. 18, and our refined U 11 for Ge is also larger than previously reported. However, the previous study did report a strong anisotropy for the displacement parameters of Ge, and a similar U 33 to that shown in Table II was reported.…”
supporting
confidence: 89%
“…Fe 3 GeTe 2 is an itinerant ferromagnet, with Curie temperatures of 220 and 230 K reported, and an estimated spontaneous magnetization of 1.6µ B /Fe at 0 K. 1,18 Previous anisotropic magnetization measurements on crystals grown using chemical vapor transport suggested that the c-axis is the easy axis, and an anisotropy field of at least 5 T was demonstrated at 10 K. 1 The Fe(2) position was reported to have a small concentration of vacancies (17%), but chemical characterization suggested the composition is Fe 3 GeTe 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations